CHARCOAL IDENTIFICATION AND AMS RADIOCARBON AGE DETERMINATION OF SAMPLES FROM SPOON LAKE 3 (YAK-076) AND KNIGHT ISLAND NORTH POINT (YAK-205), YAKUTAT COUNTY, ALASKA - Kováčik, Peter (PaleoResearch Institute) (the Digital Archaeological Record)
Sites YAK-076 (Spoon Lake 3) and YAK-205 (Knight Island North Point) lie in Yakutat Bay, southeastern Alaska. Both sites consist of house pits with hearths and associated storage caches. Recovered artifacts indicate fishing, hunting, meat and hide processing. The Spoon Lake 3 site probably was occupied as soon as AD 1275, while the settlement at the Knight Island North Point site followed shortly after glacier retreat (AD 1500) from the island (Aron Crowell, personal communication November 21, 2016). Seven charcoal samples collected from features at YAK-076 and a single feature at YAK-205 were submitted for identification. Five charcoal samples were selected for AMS radiocarbon age determination.